Igualdade de oportunidades no mercado de trabalho brasileiro sob uma perspectiva espacial - Georgia Fernandes Barros (2014)
This thesis aims to study theoretically and empirically the measurement and the spatial distribution of opportunities in the labor market through the construction of an index of equality of opportunities for 2000 and 2010, seeking to understand the distribution of job opportunities within Brazilian municipalities and its multiple dimensions over time. Contributes to the development of the concept of equality of opportunities by proposing a more aggregated analysis reflected at the local level and is distinguished by the proposed multidimensional approach, covering the sides of the supply, demand and access to services to analyze the labor market. Furthermore, undertakes an analysis that considers possible spatial spillovers of opportunities. The central hypothesis is that the distribution of opportunities in the labor market is unequal in the Brazilian space, although have been reduced over time. In terms of methodology, are built the Global Equal Opportunity Index and its component indexes, the Index of Development of Families adapted to municipalities, the Index of Labor Market Functioning and Access to Services Index, which show improvement between 2000 and 2010. When considering the spatial distribution of the indexes and their relationship with the economies of urban agglomeration, we find a process of decentralization of the IDF and of the IAS toward smaller municipalities and municipalities classified in smaller hierarchy. Moreover, by analyzing the characteristics of labor demand, we find a concentration in municipalities classified in larger sizes and greater centrality. Given these relationships, the variation of the equality of opportunities index, in turn, is distributed more evenly between the typologies adopted by municipalities (population size and hierarchy), although it had lower averages for the larger municipalities and metropolises. The spatial autocorrelation reveals spatial concentration of the indices considered, and in particular, that there are regional patterns in municipalities with high achievement and access to opportunities that relate to the opportunities present in neighboring municipalities and vice versa. Moreover, when considering local spatial autocorrelation for the variation of each index, the highest growth rates occur in the northeastern and northern regions of the country, for all indexes except for Labour Market Functioning Index, whose evolution reflects confirmation of a pattern of polarization of labor demand in the South and Southeast regions. Thus, overall, there is a reduction in inequality of opportunity in this period, with converged access and realization of opportunities, in particular with regard to the North and Northeast regions. The general conclusion is that inequality of opportunities in the labor market in Brazilian municipalities is high, but they have been reduced over time and space. The proposed indexes allow therefore capturing simultaneously the evolution and the spatial distribution of the characteristics of supply, demand and access to services and therefore providing a broader understanding of access and achievement of opportunities in the labor market as well as the mismatch between these forces. Allow, in addition, to verify that the spatial dimension of inequality appears to be essential to the understanding of labor opportunities, being relevant to the understanding of disparities and to propose public policies.